Pynchon´s parable: The american dream in The crying of Lot 49 - Meyers Skredsvig, Kari (Universidad de Costa Rica, 2015)
Aunque el estilo innovador de Thomas Pynchon La subasta del lote 49 es a la vez el deleite y la desesperación de sus lectores, su impacto se deriva del contenido mitopoética y contexto histórico en esta novela corta, Pynchon se une a las filas de los  escritores estadounidenses que exploran la individual y nacional identidad en términos de la mitología social.Although the innovative style of Thomas Pynchon's The Crying of Lot 49 is both the delight and the despair of its readers, its impact derives from the mythopoetic content and historical contexto in this short novel, Pynchon joins the ranks of U.S. writers who explore individual and national identity in terms of social mythology.